Diosgenin-3,6-dione: second polymorph in space group P212121 - Gabriel Guerrero-Luna; Jaquelin Reyes Melchor; Sylvain Bernès; María-Guadalupe Hernández-Linares (IUCrData, 2020)
The title steroid, [(25R)-spirost-4-en-3,6-dione, C27H38O4], is obtained by oxidation of diosgenin, using the Jones reagent (CrO3/H2SO4). The crystal structure was previously reported in space group P212121, but nonetheless with the wrong absolute configuration and omitting positions for H atoms [Rajnikant et al. (2000). Mol. Cryst. Liq. Cryst. Sci. Technol. Sect. C, 12, 101–110]. The diffraction data set reported herein is for a second polymorph in the same space group, as evidenced by simulated powder patterns. Both forms are characterized by a similar orthorhombic unit cell, and a similar arrangement of the molecules in the crystal structure. However, the conformation of the A/B rings in the steroid nucleus is slightly modified, leading to the observed polymorphism.